Rationale, design features, and baseline characteristics: The Heart Institute of Japan-PRoper level of lipid lOwering with Pitavastatin and Ezetimibe in acute coRonary syndrome (HIJ-PROPER). Issue 3 (March 2017) - Kawada-Watanabe, Erisa; Ogawa, Hiroshi; Koyanagi, Ryo; Arashi, Hiroyuki; Yamaguchi, Junichi; Matsui, Kunihiko; Hagiwara, Nobuhisa
Abstract: Background: In contrast to current guidelines in Western countries, moderate reduction of low-density lipoprotein cholesterol (LDL-C) is recommended for Japanese patients with atherosclerotic cardiovascular disease and dyslipidemia even in secondary prevention. HIJ-PROPER (Heart Institute of Japan-PRoper level of lipid lOwering with Pitavastatin and Ezetimibe in acute coRonary syndrome) is a prospective, randomized, open-label, blinded endpoint multicenter trial designed to assess whether closely controlled LDL-C lowering with a standard statin dose plus ezetimibe, targeting LDL-C of <70 mg/dL, would reduce cardiovascular events more than standard statin monotherapy targeting LDL-C of <100 mg/dL as per the Japan Atherosclerotic Society guideline in patients with acute coronary syndrome (ACS) and dyslipidemia. Methods: We recruited patients with ACS and dyslipidemia who had undergone coronary angiography. Participants are randomly allocated to either intensive LDL-C lowering treatment (target LDL-C of <70 mg/dL; pitavastatin plus ezetimibe) or standard LDL-C lowering treatment (target LDL-C of 90–100 mg/dL; pitavastatin monotherapy). The primary endpoint is a composite of total death, non-fatal myocardial infarction (MI), non-fatal stroke, unstable angina, and any ischemia-driven revascularization. Patients will be followed for a minimum of 3 years. Results: Between January 2010 and April 2013, 1734 patients were enrolled from 19 hospitals in Japan with a mean age of 65.6 years; 75.5% were men and 83.3% were statin-naïve. The qualifying ACS was an acute MI in 61.5%. This study is expected to report its findings in August 2016. Conclusion: HIJ-PROPER will determine whether targeting LDL-C of <70 mg/dL with pitavastatin plus ezetimibe can improve cardiovascular outcomes in Japanese patients with ACS and dyslipidemia in comparison to targeting LDL-C of 90–100 mg/dL with standard pitavastatin monotherapy. Trial registration: UMIN000002742.